Branko Milanovic. Capitalism, alone. The future of the system that rules the world. Cambridge (Mass.) y Londres, The Belknap Press of Harvard University Press, 2019, 286 pp. ISBN: 9780674987593. - Artola Blanco, Miguel (Investigaciones de Historia Económica, 2025)
Sin resumen